Study of quality of life and its patterns in different stages of menopause for women in Tehran - Golyan Tehrani; Sh. Mir Mohammad Ali; M. Mahmoudi; M. Khaledian; Z (Tehran University of Medical Sciences, 2002)
Menopause is a physiological change for women, which occurs between 40-59 years of age and has a great impact on their life quality and its patterns. This is a descriptive and analytic research, which was carried out to assess the impact of menopause and some socio-demographic and medical variables on quality of life and its patterns in Tehran in 2001. Samples were taken at random from 210 healthy women aged between 40 to 60 years and in four groups: pre-menopausal, about menopausal, menopausal and post-menopausal women with duration of less than or more than 5 years. The data was collected via a special questionnaire through interview. Analysis of data has been done by using SPSS Statistical tests 2, Bonferroni and LSD. The findings show that quality of life and its patterns were related to the menopausal stage with the highest percentage related to pre-menopausal women and the lowest to post-menopausal with a duration of 5 five years (p<0/0001). The results of the study were affected by different factors such as menopausal signs, marital situation and the age of the samples but there was no relationship with duration of the menopause, job, education, financial situation of the women, the age of the woman's first menstruation, and the number of children staying with the family. According to the findings, it is suggested that the health program designers and decision makers develop special plans to enhance women's quality of life and patterns, especially women who are about menopausal age (the first five years).